PENGARUH GOOD CORPORATE GOVERNANCE, EARNINGS PERSISTENCE, DAN ACCOUNTING CONSERVATISM TERHADAP EARNINGS QUALITY - Henryanto Wijaya (Jurnal Bina Akuntansi, 2020)
The purpose of this research is to analyze the effect of audit committee, board independence, managerial ownership, earnings persistence, and accounting conservatism on earnings quality. This research uses manufacturing industries listed in Indonesian Stock Exchange for the period 2016-2018 as the population. Using purposive sampling technique, 168 data are selected as samples. The result of ordinary least square regression analysis using IBM SPSS Statistics 23 shows that the impact of earnings persistence on earnings quality is significant. While, audit committee, board independence, managerial ownership, and accounting conservatism show no significant effect on earnings quality.